2020
DOI: 10.1101/2020.04.12.20059709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethanol-Drying Regeneration of N95 Respirators

Abstract: A critical shortage of respirators, masks and other personal protective equipment (PPE) exists due to the COVID-19 pandemic. Of particular need are N95 respirators, which use meltblown microfibers of charged polypropylene. An intensive search is underway to find reliable methods to lengthen the useful life of these normally disposable units. Recent experiments on respirators cleaned with ethanol solutions found drastic post-treatment drops infiltration efficiency (>40%). This has been attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…This drop in filtration efficiency can be restored using methods such as triboelectric charging, [ 47 ] and vacuum filtration. [ 48 ] We report a similar observation, when samples treated in 75% ethanolic nanocomposite solutions of varying concentrations were dried overnight in a vacuum oven, the filtration efficiency was restored closer to the initial value for bare untreated filter media. We also observed that on increasing the concentration of Cu@ZIF‐8 NWs beyond 0.25 mg mL −1 , the filtration efficiency surpassed the efficiency of bare filter media.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…This drop in filtration efficiency can be restored using methods such as triboelectric charging, [ 47 ] and vacuum filtration. [ 48 ] We report a similar observation, when samples treated in 75% ethanolic nanocomposite solutions of varying concentrations were dried overnight in a vacuum oven, the filtration efficiency was restored closer to the initial value for bare untreated filter media. We also observed that on increasing the concentration of Cu@ZIF‐8 NWs beyond 0.25 mg mL −1 , the filtration efficiency surpassed the efficiency of bare filter media.…”
Section: Resultssupporting
confidence: 70%
“…This drop in filtration efficiency can be restored using methods such as triboelectric charging, [47] and vacuum filtration. [48] We report a similar observation, when samples treated in 75% ethanolic nanocomposite solutions of varying concentrations were…”
Section: (5 Of 13)supporting
confidence: 65%
See 1 more Smart Citation
“…In the case of disinfection with ethanol-based solutions, recent preliminary work also shows that vacuum drying may be able to restore the efficiency of FFRs. 33 It is also possible that the chlorine-based solution may degrade the efficiency less than the alcohol-based solution due to the higher water content. As polypropylene is hydrophobic, the chlorine-based solution may have a more difficult time penetrating the fabric and the static charge of fibers deeper within the meltblown may be less affected.…”
Section: Resultsmentioning
confidence: 99%
“…This efficiency is shown to get lower for smaller particles sizes. Moreover, most of the existing face masks are hydrophilic and inefficient when wet where their performance in repelling water droplets and allowing appropriate respiration degrades [21]. Another important characteristic of face masks is the breathability.…”
Section: Introductionmentioning
confidence: 99%